1987
DOI: 10.1016/0014-5793(87)80255-7
|View full text |Cite
|
Sign up to set email alerts
|

Binding of synthetic β‐human atrial natriuretic peptide to cultured rat vascular smooth muscle cells

Abstract: We have studied the effects of synthetic p-human atria1 natriuretic peptide (j?-hANP), an antiparallel dimer of a-hANP, on receptor binding and cGMP generation in cultured rat vascular smooth muscle cells and compared the effects with those of a-hANP. Characteristics of temperature-dependent binding and degradation of 1Z51-~-hANP were similar to those of lZSI-a-hANP. Scatchard analysis indicated a single class of binding sites for b-hANP with a maximal binding capacity one-half that of a-hANP. Parallel and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In addition, a dicarba analog β ‐ANP acts as antagonist against α ‐ANP and inhibits the α ‐ANP‐induced cyclic guanosine monophosphate production in a dose‐dependent manner . These observations are consistent with the lower affinity of β ‐ANP to NPR‐A; the maximal binding capacity of β ‐ANP to the receptor is one‐half that of α ‐ANP .…”
Section: Introductionsupporting
confidence: 68%
“…In addition, a dicarba analog β ‐ANP acts as antagonist against α ‐ANP and inhibits the α ‐ANP‐induced cyclic guanosine monophosphate production in a dose‐dependent manner . These observations are consistent with the lower affinity of β ‐ANP to NPR‐A; the maximal binding capacity of β ‐ANP to the receptor is one‐half that of α ‐ANP .…”
Section: Introductionsupporting
confidence: 68%
“…1). In contrast to&ANP, which tends to be converted into cr-ANP when incubated with human plasma [5] or cultured rat VSMC [6], analog III does not under-go such conversion under the usual physiological conditions because of the presence of an Asu residue in the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…&ANP is also known to be converted into cu-ANP when incubated with human plasma [5] or rat cultured vascular smooth-muscle cells (VSMC) [6]. In view of these facts, Itoh et al [5] suggested that the slow onset and long-acting property of P-ANP was a consequence of its slow conversion into a-ANP.…”
mentioning
confidence: 99%
“…The study suggested that cGMP egression appears to be mainly an active transport process which is temperature-dependent. In cultured vascular smooth muscle cells, the decrease in receptor bound 125 I-labeled ANP due to internalization, degradation, and elimination of ligands was more rapid at 37°C than that at 4°C (15). A more recent FIG.…”
Section: Discussionmentioning
confidence: 94%